An Analysis of Sumbawa University of Technology Nusantara Students’ Motivation to Study Sumbawa Language - Iman, Topan Rahmatul (JETAL: Journal of English Teaching & Applied Linguistic, 2024)
Sumbawa University of Technology is one of the universities in Indonesia. According to the data from the head of Sumbawa University of Technology students’ admission (Mustaram, personal communication, March 21, 2024), the students of UTS come from 28 provinces in Indonesia. It is assumed that this condition impetuses the students to learn the local language, which is the Sumbawa language. Therefore, the aim of this study is to look at the motivation of Sumbawa University of Technology Nusantara students to study the Sumbawa language. The design of this study was descriptive quantitative research. There were 7 students completed the questionnaire. The data was analyzed in five steps; scoring, adding up, determining the mean, categorizing the mean, and interpreting the mean. There are two motivations for UTS Nusantara students to study the Sumbawa language: intrinsic and extrinsic factors. The intrinsic motivation consists of personal interests and enjoyment of language learning, such as the desire to add linguistic knowledge, interact with Sumbawa people, and avoid discomfort with locals. Extrinsic motivation relates to external rewards or social approval such as the desire to live in Sumbawa, work in Sumbawa, get networking opportunities, and be asked by others to learn the Sumbawa language.